Paradigm in the Catholic Schooling for Liberation Through the Montfort Ideology in the Thai Context - Wipakthamrongkun, Anuwat (Scholar: Human Sciences, 2021)
In order to fully develop all human dimensions and live a life with full dignity of humanity; To liberate themselves to achieve freedom on the basis of individual experience towards the social and cultural contexts (Brothers of Saint Gabriel 1986: 38); With a principle called "Means to acquire divine Wisdom". There are four principles of practice as follows: 1) Ardent desire 2) Contemplatives 3) Reflection 4) Self-Dedication (Brothers of Saint Gabriel, 1987: 100-110) to be able to access, understand the reality of life and create a new meaning to be a perfect holistic person who can live in a diverse society.